Implementasi Evaluasi Model Context, Input, Process & Product (Cipp) Dalam Pembelajaran Praktik Berbasis Virtual Pada Laboratorium Sistem Tenaga Listrik - Dwi Anggaini; Titi Ratnasari; Intan Ratna Sari Yanti (KILAT, 2023)
This goals as a shape of assessment of laboratory-primarily based totally realistic getting to know for guides completed withinside the Power System Analysis laboratory. This form of studies is a application assessment studies with a descriptive quantitative studies approach. The approach in accumulating studies statistics is with the aid of using the usage of a questionnaire given to academics and college students who take the AST direction practicum according with the Context, Input, Process & Product (CIPP) version assessment instrument, similarly to the questionnaire statistics series is completed with the aid of using commentary throughout the practicum. In this have a look at there had been eleven instructors and 15 college students who had been used as samples. From the sample, it indicates that the cost acquired with the aid of using the practicum lecturer in phrases of contextual is 84.090%, in phrases of enter is 90.150%, in phrases of technique is 89.770% and in phrases of product is 87.12%. From the scholar aspect, the effects finished primarily based totally at the expertise of realistic getting to know withinside the laboratory in phrases of contextual are 80.00%, in phrases of enter 83.660%, in phrases of technique 85.830% and 79.160% in phrases of product. Based at the effects of calculations from the aspect of the lecturer and college students that digital laboratory-primarily based totally realistic getting to know goes properly in order that college students` expertise is withinside the properly category.